Procalcitonin-Guided Treatment on Duration of Antibiotic Therapy and Cost in Septic Patients (PRODA): a Multi-Center Randomized Controlled Trial - Jeon, Kyeongman; Suh, Jae Kyung; Jang, Eun Jin; Cho, Songhee; Ryu, Ho Geol; Hong, Sang-Bum; Lee, Hyun Joo; Kim, Jae Yeol; Lee, Sang-Min (Journal of Korean medical science, 2019)
The objective of this study was to establish the efficacy and safety of procalcitonin (PCT)-guided antibiotic discontinuation in critically ill patients with sepsis in a country with a high prevalence of antimicrobial resistance and a national health insurance system. In a multi-center randomized controlled trial, patients were randomly assigned to a PCT group (stopping antibiotics based on a predefined cut-off range of PCT) or a control group. The primary end-point was antibiotic duration. We also performed a cost-minimization analysis of PCT-guided antibiotic discontinuation. The two groups (23 in the PCT group and 29 in the control group) had similar demographic and clinical characteristics except for need for renal replacement therapy on ICU admission (46% vs. 14%; = 0.010). In the per-protocol analysis, the median duration of antibiotic treatment for sepsis was 4 days shorter in the PCT group than the control group (8 days; interquartile range [IQR], 6-10 days vs. 14 days; IQR, 12-21 days; = 0.001). However, main secondary outcomes, such as clinical cure, 28-day mortality, hospital mortality, and ICU and hospital stays were not different between the two groups. In cost evaluation, PCT-guided therapy decreased antibiotic costs by USD 30 (USD 241 in the PCT group vs. USD 270 in the control group). The results of the intention-to-treat analysis were similar to those obtained for the per-protocol analysis. PCT-guided antibiotic discontinuation in critically ill patients with sepsis could reduce the duration of antibiotic use and its costs with no apparent adverse outcomes. ClinicalTrials.gov Identifier: NCT02202941.